User acceptance studies for LED office lighting: Lamp spectrum, spatial brightness and illuminance. (February 2015) - Islam, MS; Dangol, R; Hyvärinen, M; Bhusal, P; Puolakka, M; Halonen, L
In order to determine user acceptance for light-emitting diode (LED) office lighting, a full-scale experiment was conducted in two mock-up office rooms with different light spectra at two different illuminances. Six LED spectra and two fluorescent lamp spectra were used for the study. There were four spectra (three LED spectra and one fluorescent lamp spectrum) at a correlated colour temperature (CCT) of 4000 K and four spectra (three LED spectra and one fluorescent lamp spectrum) at a CCT of 6500 K. Forty observers evaluated the lighting environments under different spectra and rated the lighting environments sitting at a working desk and at a meeting table. The observers preferred the task illuminance of 500 lux to 300 lux and the CCT of 4000 K to 6500 K. The observers preferred the spectral power distributions (SPDs) under which they found the lighting environment to look brighter and more spacious. The observers' preferences showed that spatial brightness was affected by illuminances and SPDs. The lighting with a SPD having higher values of a reference-based metric (CQS Colour Preference Scale) and an area-based metric (CQS Gamut Area Scale or Gamut Area Index) was preferred most at a CCT of 4000 K. It was also found that the lighting with the fluorescent lamp was least preferred among the other SPDs at the CCT of 4000 K. The observers preferred both the simple and complex SPDs over fluorescent lamps at 4000 K in the office environment. It would be a good option to develop simple LED SPDs while maintaining the criteria of good lighting for an office environment.